Escola Superior de Artes Visuais - Liborio, Kelvia Veras (Brasil, 2023)
This work intends to carry out studies and surveys in the Adrianópolis neighborhood of information that are useful for the development of a project of a college with a focus on teaching visual arts, demonstrating how this type of work can positively impact the future artists of Manaus and how the city can value art more.